Обеспечение конфиденциальности информации в облачных системах - Шаповалов, И. В.; Добрынин, И. С. (ХНУРЭ, 2011)
Cloud computing is a fast developing technology in which information is stored and processed on the remote servers. Security of the information, which is stored and processed in cloud systems, is important part of this new technology. According to social analysis, security of the information and trusting to the service providers are the most important problems of cloud computing. This work represents methods of securing data, which is stored in the cloud.
Keywords: провайдер услуг; облачные технологии